ANALYSIS OF INDONESIAN-ENGLISH CODE SWITCHING AND CODE MIXING ON FACEBOOK - Zalukhu, Ade Andi Firman; Laiya, Rebecca Evelyn; Laia, Mohammad Yunus (Universitas Nias Raya, 2021)
This research aimed to analyze the types of code switching and code mixing and describe the reason of using them on facebook. This research designed by qualitative research with content analysis approach. The data were collected by documentation and interview. Based on data analysis there were 47 code switching and 61 code mixing. The types of code switching there were 14 data of intrasentential switching, 3 data of tag switching and 30 data of intersentential swicthing. The types of code mixing there were 43 data of insertion, 14 data of alternation and 4 data of congruent lexicalization. For the reasons that affected of using code switching and code mixing, there were indicating the level of education, to show prestige and to draw attention. As the result of research finding, intersentential switching and insertion are the most types that used on the facebook. the researher proposed a suggestion for the students to enrich their knowledge about sociolinguistics concerning code switching and code mixing and also as the source for the next researcher and the reader.